DEISME DARI EDWARD HERBERT SAMPAI DAVID HUME - Shofiyullah Muzammil (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
This paper discusses three important thing related to deism, especially deism that developed in England. First, the emergence deism is started by Edward Herbert ideas in 1624, as consequence  and influence of the situation and condition at that time. Second, it is the growth of deism in early seventeenth century, especially by the influence of philosophy that developed by John Locke. Third, it is the rapid decline of deism after second half of seventeenth century because of David Hume's skepticism. This paper will start by the description of definition of deism, characteristic, and historical development of deism, followed by the explanation of main background that influenced its emergence. Moreover, this paper will move to the proponents of deism and their ideas which are include three different eras: the era of pioneering  from Herbert to Blount (1624-1695); the era of glory from Toland to Tindal (1696-1741); and the era of declining fromAnnet to Bolingbroke (1742-1770).